Preparation, Characterization, and Evaluation of Breviscapine Nanosuspension and Its Freeze-Dried Powder - Ting Zhang; Xixi Li; Juewen Xu; Jingbao Shao; Meihong Ding; Senlin Shi (MDPI AG, 2022)
As a biopharmaceutics classification system (BCS) class IV drug, breviscapine (Bre) has low solubility in water, poor chemical stability, a short biological half-life and rapid removal from plasma. This paper prepared a Bre nanosuspension (Bre-NS) by an ultrasound-assisted anti-solvent precipitation method. Characterization of Bre-NS was studied using a Box-Behnken design concerning drug concentration in DMSO, an anti-solvent-to-solvent ratio, and sonication time. Under the optimized conditions of 170 mg/mL for the drug concentration, a 1:60 solvent-to-anti-solvent ratio, and a 9 min sonication time, the particle size of Bre-NS was 303.7 ± 7.3 nm, the polydispersity index was 0.178 ± 0.015, and the zeta potential was −31.10 ± 0.26 mV. Combined with the results from differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and Fourier transform-infrared spectroscopy (FT-IR), the findings indicated that the crystal form and chemical structure of Bre-NS did not change during the entire process. The optimized formulation displayed good stability, increased solubility, and better in vitro release. Therefore, the results of this study can be a reference for the delivery system design of insoluble active components and effective parts in traditional Chinese medicine.